Models for the study of family businesses (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2025)
This article aimed to conduct a theoretical review of models for the study of family businesses, motivated by the importance these types of organizations hold in the economy and the business world. The research was developed using a qualitative approach with a documentary and descriptive research design, carried out in four phases. The process emphasized reviewing and analyzing bibliographic sources, starting with various definitions of family businesses, their characteristics, and taxonomy. It then focused on developing models for studying family businesses, specifically limiting the scope to circular models and time or life cycle models due to the extensive nature of the topic. Among the study's conclusions, notable points include the extensive research trajectory in this type of organization, the contributions of various authors reflected in different models, and the systemic vision of the family business through subsystems or circles and their interaction and interdependence. Additionally, it highlighted the broad elements that constitute definitions such as capital, ownership, and management, and emphasized the need to maintain a balance between the family and the business as well as fostering family harmony.
Keywords: family businesses; models; general systems theory